Sensor fault tolerant controller for a double inverted pendulum system - Yang, S.S.; Chen, J.; Mohamed, H.A.F.; Moghavvemi, M. (2008)
This paper presents an Internal Model Control based structure to realise fault tolerance towards sensor faults. The proposed design implicitly embeds fault detection and controller elements requirements with considerations to stability and robustness towards uncertainties besides multiple faults environment. The performance of the proposed controller is demonstrated via multi input multi output and unstable system i.e. the double inverted pendulum system. Performance of the controller is compared with the well known H controller. Results show the potential of this controller for implementation to handle systems with multiple sensor faults and uncertainties.